A report on the perseptions of participants of a physiotherapy clinical facilitator workshop - A. Frieg; A. Rhoda (AOSIS, 2006)
Clinical education is the cornerstone of the training of health professionals.  Many training institutions offer courses in clinical education.  Fifteen participants of a 20-hour physiotherapy clinical facilitators workshop formed part of this descriptive study.  The aim of the study was to evaluate their perceptions of the workshop and the impact it had on their practice.  Data were captured using three separate questionnaires, consisting of closed- and open-ended questions. Descriptive statistics were used to analyse the data.  Results indicated that participants regarded the topics presented as important, that their needs had been met and that they enjoyed the workshop immensely. Furthermore, they reported that the content of the workshop had an impact on their practice.  Many participants requested follow-up workshops on clinical education.  It can be concluded from the above results that a workshop addressing educational aspects is an appropriate method of supporting colleagues involved in physiotherapy clinical training.